2019
DOI: 10.1063/1.5116210
|View full text |Cite
|
Sign up to set email alerts
|

A demonstration of consistency between the quantum classical Liouville equation and Berry’s phase and curvature for the case of complex Hamiltonians

Abstract: Although the quantum classical Liouville equation (QCLE) arises by cutting off the exact equation of motion for a coupled nuclear-electronic system at order 1 (1 = 0 ), we show that the QCLE does include Berry's phase effects and Berry's forces (which are proportional to a higher order, = 1 ). Thus, the fundamental equation underlying mixed quantum-classical dynamics does not need a correction for Berry's phase effects and is valid for the case of complex Hamiltonians. Furthermore, we also show that, even thou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…Recent dynamical work has suggested that the imaginary component of NADCs can yield very rich new physical behaviors. 42 In particular, whenever the derivative coupling d is complex, such complexity automatically introduces nontrivial Berry phase effects, 72,73 whereby a given trajectory moving on adiabat J with momentum ⃗ p should feel a force, 42,74…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent dynamical work has suggested that the imaginary component of NADCs can yield very rich new physical behaviors. 42 In particular, whenever the derivative coupling d is complex, such complexity automatically introduces nontrivial Berry phase effects, 72,73 whereby a given trajectory moving on adiabat J with momentum ⃗ p should feel a force, 42,74…”
Section: Discussionmentioning
confidence: 99%
“…the real/imaginary nature of the NADC because if the NADC is truly imaginary, we should find interesting Berry phase physics. 42,74 However, it is clear (disappointingly) that in practice, for the case of benzaldehyde, after rotation there are little to no remaining imaginary components, and the NADCs can be rotated into an almost entirely real-valued vector; thus, no Berry phase effects will be strong here, using the formula in Eq. ( 50).…”
Section: Article Scitationorg/journal/jcpmentioning
confidence: 99%
“…Note that another branching criterion was recently proposed by Shi and coworkers 49 and may be useful to further improve the performance of BCMF. (3) Previous studies show that the mean field approach can automatically characterize the Berry phase 58,59 and naturally treat trivial crossings, 15,19 while traditional surface hopping does not. [60][61][62][63][64][65] This also justifies the urgent demand to develop robust mean field methods like BCMF.…”
Section: Pd Ppmentioning
confidence: 99%
“…Hamiltonian, we would need to discuss Berry's force and an approximate hopping direction, 30,31 which would only complicate the present paper (and will be addressed in a future publication).…”
Section: B Testing the Algorithm With A Simple Model Problem In The mentioning
confidence: 99%